2014
DOI: 10.1155/2014/983160
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Distal Ulnar Artery Thrombosis

Abstract: This paper is about a posttraumatic distal ulnar artery thrombosis case that has occurred after a single blunt trauma. The ulnar artery thrombosis because of chronic trauma is a frequent condition (hypothenar hammer syndrome) but an ulnar artery thrombosis because of a single direct blunt trauma is rare. Our patient who has been affected by a single blunt trauma to his hand and developed ulnar artery thrombosis has been treated by resection of the thrombosed ulnar artery segment. This report shows that a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first case in the literature that presented with a vasculitis-like picture after trauma. Karaarslan et al have reported a case of ulnar arterial thrombosis after a trauma that presented with hand pain and swelling rather than digital gangrene [ 13 ]. “Hypothenar-hammer” syndrome has been commonly described in the literature, which refers to an injury to the ulnar artery as a consequence of repetitive trauma, which results in thrombosis and embolism of digital arteries.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first case in the literature that presented with a vasculitis-like picture after trauma. Karaarslan et al have reported a case of ulnar arterial thrombosis after a trauma that presented with hand pain and swelling rather than digital gangrene [ 13 ]. “Hypothenar-hammer” syndrome has been commonly described in the literature, which refers to an injury to the ulnar artery as a consequence of repetitive trauma, which results in thrombosis and embolism of digital arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In the HHS, the ulnar artery segment of over 2 cm which lies immediately distal to the Guyon canal before reaching the palmar aponeurosis, is the damaged segment. This segment of the ulnar artery is susceptible to injury due to its superficial location and limited protection of the soft tissues overlying it [9,10]. Repeated blunt trauma may induce intimal damage to the vasospasm in the superficial palmar segment of the ulnar artery and trigger platelet aggregation and thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes include fractures, crush injuries, and penetrating wounds that change the intima of the artery. Precise identification of an arterial blockage as embolic or thrombotic is essential before effective treatment can begin [3]. Arterial emboli are most usually caused by thrombi that form in the heart chambers as a result of arterial fibrillation or myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%